2008
DOI: 10.1177/1555412008325480
|View full text |Cite
|
Sign up to set email alerts
|

The Gray Haired Gaming Generation

Abstract: The market for adult computer gamers is growing considerably. However, there are nearly no empirical works that are primarily focusing this age group. Therefore, there is an urgent need for explorative studies on these gamers. In a qualitative in-depth interview study with 21 gamers aged between 35 and 73 years, this article describes their gaming careers, the integration of gaming into their everyday life, and aspects of social interaction within real and virtual life. Overall, the findings of this study sket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 6 publications
1
21
0
3
Order By: Relevance
“…Experienced older gamers are social, community-oriented gamers, and special emphasis is placed on social contacts, mutual help during the game, sharing games objectives, chatting about everyday topics during the game sessions, and/or being connected to one's significant other. [6][7][8] In relation to social play, older people seem to prefer co-located play (in the same room) above social play over the Internet (i.e., mediated play). An experimental study of Gajadhar et al 9 found that seniors' player experience during social play is most positive in co-located play and solo play, whereas the least enjoyment is experienced in mediated play without means for face-to-face interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Experienced older gamers are social, community-oriented gamers, and special emphasis is placed on social contacts, mutual help during the game, sharing games objectives, chatting about everyday topics during the game sessions, and/or being connected to one's significant other. [6][7][8] In relation to social play, older people seem to prefer co-located play (in the same room) above social play over the Internet (i.e., mediated play). An experimental study of Gajadhar et al 9 found that seniors' player experience during social play is most positive in co-located play and solo play, whereas the least enjoyment is experienced in mediated play without means for face-to-face interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, looking at eSports and related phenomena, Simon (2013) refers to fight gamers, or those who play fighting games, as a distinct culture and community separate from eSports. Finally, Quandt, Grueninger and Wimmer (2008) observe adult players of several games, who belong to various game communities and cultures. Hence, as seen from the work of several academics, a meso level approach to game culture is possible when there is a unifying factor present, whether it is between the participants (age or gender), the genre of game, or method of play (console or PC, modding or speed running).…”
Section: Digital Game Cultures From a Theoretical Perspectivementioning
confidence: 99%
“…Hence, as seen from the work of several academics, a meso level approach to game culture is possible when there is a unifying factor present, whether it is between the participants (age or gender), the genre of game, or method of play (console or PC, modding or speed running). The unifying factor doesn't necessarily have to relate to the game itself (Lin & Sun, 2007;Taylor, 2006) but it can also be a factor associated with gamers (Quandt et al, 2008), or the community (Simon, 2013). Utilizing a definition of game culture on a macro level attempts to characterize the entirety of gamers (and certain aspects of their culture) as a whole.…”
Section: Digital Game Cultures From a Theoretical Perspectivementioning
confidence: 99%
“…There is value in knowing the demographic distribution of Chinese MMO player population, as evidence regularly suggests a strong influence of demographic attributes such as age and gender on players' in-game behavior, experience and motivations (Eden, Maloney, & Bowman, 2010;Quandt, Grueninger, & Wimmer, 2009;Williams, Consalvo, Caplan, & Yee, 2009). Players' virtual behaviors are also directly related to where they play (physical locations) and how they play (with friends) (Chee, 2006;Jiang, 2008).…”
Section: Demographicsmentioning
confidence: 99%